A novel LC-MS/MS method development and validation for the determination of tezepelumab in rat plasma and its application in rat pharmacokinetic studies - Madhusudhan Reddy Nimmakayala, Deepti Kolli, Murali Prakash Jatla (Journal of Applied Pharmaceutical Science, 2024)
By developing a quick, accurate, reproducible, and straightforward liquid chromatography-tandem mass spectrometry (LC-MS/MS) system and employing trastuzumab as an internal standard, tezepelumab (TZP) quantification was achieved. This study explores the most recent advancement in bioanalytical LC-MS/MS technologies utilizing a 150 × 4.6 mm, 3.5 μ Waters Symmetry C18 column that was set for isocratic mode at ambient temperature. Methanol (MeOH): 0.1% formic acid in 40:60 v/v at 1.0 ml/minute was utilized as the mobile phase. The injection volume and runtime were 10 μl and 5 minutes, respectively. TZP’s retention time was 1.944 minutes, and a chromatographic duration total of 5.0 minutes. With a correlation value (r2) of 0.99971, the technique was validated for TZP throughout a linear range of 6.00–120.00 ng/ml. Findings for precision, accuracy, recovery, matrix effect, and stability all occurred within acceptable limits. Below the visual abstract is the concise summary of the article.
Keywords: Tezepelumab, trastuzumab, USFDA, rat plasma, LC-MS/ MS